Resilience and Spiritual well being in Rural and Urban Communities: A Community Nursing Perspective - Zaini, Mad; Supapak Phetrasuwan; Komarudin (Journal Of Nursing Practice, 2026)
Background: Resilience and spiritual well-being are essential aspects of life in both rural and urban settings. Rural communities are more closely connected to nature, yet they face limitations in accessing health care services. In contrast, urban communities experience stress related to social life, but they benefit from more access to health. Purpose: This study aims to examine differences in resilience and spiritual well-being in rural and urban communities in Jember Regency. Methods: The researchers employed a cross sectional approach for analyzing the study. The sample consisted of 210 respondents living in rural and urban communities in Jember Regency. The researchers selected the samples using a purposive sampling technique. Data collection was carried out using a digital questionnaire through validity and reliability tests. Data were analyzed using independent sample t-test. Results: Univariate test results indicate that the mean resilience score for rural communities is 64.70, whereas for urban communities it is 64.81. The mean spiritual well-being score for rural communities is 22.35, compared to 22.86 for urban communities. The difference test for resilience between rural and urban communities yields a p-value of 0.92, while the spiritual well-being difference test shows a p-value of 0.11. Conclusion: The conclusion of this study is that there is a relationship between resilience and spiritual well-being in rural and urban communities in Jember Regency. Meanwhile, the results of the difference test for resilience and spiritual well-being showed no difference between rural and urban communities.